Effect of Ultraviolet-Ozone Treatment on MoS2 Monolayers: Comparison of Chemical-Vapor-Deposited Polycrystalline Thin Films and Mechanically Exfoliated Single Crystal Flakes - Changki Jung; Hae In Yang; Woong Choi (Nanoscale Research Letters, 2019)
Abstract We report the different oxidation behavior between polycrystalline chemical-vapor-deposited and mechanically exfoliated single crystal MoS2 monolayers by ultraviolet-ozone treatment. As ultraviolet-ozone treatment time increased from 0 to 5 min, photoluminescence emission and Raman modes of both MoS2 disappeared, suggesting structural degradation by oxidation. Analysis with optical absorbance and X-ray photoelectron spectroscopy suggested the formation of MoO3 in both MoS2 after ultraviolet-ozone treatment. In addition, ultraviolet-ozone treatment possibly led to the formation of oxygen vacancies, molybdenum oxysulfide, or molybdenum sulfates in chemical-vapor-deposited MoS2. The measurement of electrical resistance after ultraviolet-ozone treatment suggested the transformation of chemical-vapor-deposited MoS2 into doped MoO3 and of mechanically exfoliated MoS2 into negligibly doped MoO3. These results demonstrate that the crystallinity of monolayer MoS2 can strongly influence the effect of ultraviolet-ozone treatment, providing important implications on the device integration of MoS2 and other two-dimensional semiconductors.